Belimumab in a Patient with Systemic Lupus Erythematosus with Juvenile Onset and Steroid-induced Diabetes: Clinical Case - Maria I. Kaleda; Irina P. Nikishina; Alesya V. Firsa ("Paediatrician" Publishers LLC, 2023)
Background. The management of children with systemic lupus erythematosus (SLE) is usually associated with lifelong systemic glucocorticoids administration and, thereby, high risk of serious side effects, including steroid-induced diabetes. The belimumab (B-lymphocyte stimulator inhibitor) administration significantly reduces the glucocorticoids dose, the risk and severity of steroid therapy complications. Clinical case description. The patient was diagnosed with SLE at the age of 16 years. Therapy with hydroxychloroquine and oral glucocorticoid at a high dose (methylprednisolone 56 mg per day) was initiated. Steroid-induced diabetes was diagnosed 1 month after the therapy start; avascular necrosis sites were revealed in 2 months. Mycophenolate mofetil made it possible to achieve the disease activity control. However, the belimumab was prescribed 5 months after diagnosis verification due to continuous insulin requirement and avascular necrosis progression. Conclusion. Belimumab is the only genetically engineered biologic drug approved for the treatment of children with SLE. As a result of its use, it was possible to stabilize the patient's condition quickly (within 3 months), to reduce significantly the dose of oral glucocorticoid, methylprednisolone (from 24 to 8 mg/day), to achieve remission of steroidinduced diabetes with further insulin withdrawal, and also to relieve avascular necrosis clinical symptoms.